Beginning Excel What-If Data Analysis Tools - Cornell, Paul (Apress, 2012)
Consider the following two story problems: If I ride a bicycle 5 miles in 20 minutes, how long would it take me at that speed to ride my bicycle 20 miles? At that speed, how far could I ride my bicycle in 45 minutes? If I earn $25.00 per non-overtime hour at a job and I work 45 hours per week, how many weeks would I need to work to earn $30,000 before taxes? How much would I earn before taxes if I worked a 50-week work year and took the remaining two weeks off without pay? Here are the answers to these story problems: It would take me 80 minutes to ride my bicycle 20 miles if I were riding it 5 miles in 20 minutes (that is, 15 miles per hour). At that speed, in 45 minutes I would ride my bicycle 11.25 miles. I would need to work between 25 and 26 weeks to earn $30,000 if I earn $25.00 per hour working 45 hours per week (assuming I am paid one-and-one-half times my hourly rate for all hours worked over 40 per week). At that pace, I would earn $59,375 if I worked 50 weeks that year and took the remaining two weeks off without pay. These are a few simple examples of the types of problems that the Microsoft Office Excel what-if data analysis tools are designed to solve quickly. This book teaches you how to use these tools.